The Pythagorean theorem is a² + b² = c². Solve for b. b=±c+a−−−−√ b=±c2−a2−−−−−−√ b=±c2+a2−−−−−−√ b=±c−a−−−−√

Respuesta :

[tex] a^{2} +b^{2} =c^{2} [/tex]

As we have to solve for b, it means we have to isolate b

So first of all subtract [tex] a^{2} [/tex] from both sides

So we get

[tex] b^{2} =c^{2} -a^{2} [/tex]

Now we need b , but its b^2 , so we can take square root on both sides.


taking square roots on both sides

[tex] b= +- \sqrt{c^2 -a^2} [/tex]


Hence option B is correct

Answer:

B.  b = +- sqrt (c^2 - a^2)

Step-by-step explanation:

I just took the test!!!